First record of the genus Helvetia Peckham & Peckham, 1894 (Araneae: Salticidae: Chrysillini) from Colombia and extension of its distribution in Argentina - Bedoya-Roqueme, Edwin; Nadal, María F.; Rubio, Gonzalo Daniel (Peckham Society, 2020)
The jumping spider genus Helvetia Peckham & Peckham 1894 (Araneae: Salticidae: Chrysillini) is recorded for the first time from Colombia, with the species H. albovittata Simon 1901 associated with ant nests in mangrove forest from south of the Gulf of Morrosquillo, Caribbean Colombia. This is the first record of the genus from Colombia and the northernmost record of the genus for South America. New illustrations are shown, and additional records from Argentina are presented. A distribution map with both new and previously published records is included.